Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1096/fj.13-230706
|View full text |Cite
|
Sign up to set email alerts
|

The novel complement inhibitor human CUB and Sushi multiple domains 1 (CSMD1) protein promotes factor I‐mediated degradation of C4b and C3b and inhibits the membrane attack complex assembly

Abstract: CUB and Sushi multiple domains 1 (CSMD1) is a transmembrane protein containing 15 consecutive complement control protein (CCP) domains, which are characteristic for complement inhibitors. We expressed a membrane-bound fragment of human CSMD1 composed of the 15 C-terminal CCP domains and demonstrated that it inhibits deposition of C3b by the classical pathway on the surface of Chinese hamster ovary cells by 70% at 6% serum and of C9 (component of membrane attack complex) by 90% at 1.25% serum. Furthermore, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 35 publications
3
77
0
Order By: Relevance
“…The expression of CSMD1 was confirmed by flow cytometry analysis with a specific antibody (Figure 2Cii and 2Dii). In order to knock down the expression of CSMD1 in T47D cells, we used a ribozyme transgene generated previously in which a reduction of CSMD1 was confirmed on both the RNA and the protein levels [3]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CSMD1 was confirmed by flow cytometry analysis with a specific antibody (Figure 2Cii and 2Dii). In order to knock down the expression of CSMD1 in T47D cells, we used a ribozyme transgene generated previously in which a reduction of CSMD1 was confirmed on both the RNA and the protein levels [3]. …”
Section: Resultsmentioning
confidence: 99%
“…Human CUB and Sushi multiple domains 1 (CSMD1) is a large (∼ 390 kDa) membrane-bound complement inhibitor [3]. It is composed of 14 N-terminal CUB domains separated by single complement control protein (CCP) domains and followed by 15 consecutive CCP domains.…”
Section: Introductionmentioning
confidence: 99%
“…The function of CSMD1 is largely unknown. Although CSMD1 has been shown to inhibit C3 deposition onto the surface of cells leading to the inhibition of the classical complement pathway (4,5). The structure of CSMD1 predicts that CSMD1 is a receptor for unknown ligand(s) and is involved in signal transduction (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, exploration of the TreatOA GWAS data set for hip and for knee OA showed no association for rs9657371 (data not shown). The rat homologue of CSMD1 was identified in a search for proteins of the ‘regulators of complement activation’ family,39 and it was shown that CSMD1 blocked the classical complement pathway activation 39 40. It may therefore be speculated that innate dysregulated expression of CSMD1 results in a (slight) activation of the complement cascade in articular cartilage independent of OA, leading to changes in the release of CTX-II.…”
Section: Discussionmentioning
confidence: 99%